PENGEMBANGAN BAHAN AJAR MATA KULIAH PEMROGRAMAN VISUAL DENGAN MENGGUNAKAN PROJECT BASED LEARNING - Vera Irma Delianti; Yeka Hendriyani; Rizkayeni Marta (Universitas Negeri Padang, 2018)
This study aims to produce products that are teaching material that are learning modules for students who take the Visual Programming course. So that later students will carry out lectures with more ease and direction. The research methods used are development research methods (research and development), with the development designs chosen are using the Project Based Learning model. The steps of learning model Project Based Learning are as follows: (1) start with the big question, (2) design a plan for the project, (3) create a schedule, (4) monestudents and the progress of the project, (5) assess the outcome, and (6) evaluate the experience. The teaching materials for students and students are expected to be able to help students for more understanding of lectures Visual Programming. Over a period of time, it increased the students' learning outcomes that took the Visual Programming course